Redescription of Cerceis biforamina Javed & Yousuf, 1996 from the Gulf of Oman (Crustacea: Isopoda: Sphaeromatidae) with remarks on the status of Cymodoce insolita Yousuf, 2011 - Khalaji-Pirbalouty, Valiallah (Zootaxa, 2018)
Cerceis biforamina Javed & Yousuf, 1996 is redescribed and illustrated based on material from the Iranian coasts of the Gulf of Oman. This species is distinguished by the smooth pereonites 1–6, pereonite 7 with a row of tubercles and short setae; pleon dorsal surface with multiple prominent tubercles medially; pleotelson with two prominent semilunar tuberculate ridges and clearly trilobed posterior margin. Cerceis insolita Yousuf, 2011 is transferred to genus Cymodoce and synonymised with Cymodoce manorii (Nooruddin, 1965). An extended diagnosis is provided for the genus Cerceis.